Enhancing transnational labour solidarity: the unfulfilled promise of the Internet and social media. Issue 4 (14th September 2017) - Geelan, Torsten; Hodder, Andy
Abstract: This article examines the activities of Union Solidarity International (USI), a new UK‐based organisation in the international union arena. USI seeks to encourage and support international solidarity between trade unions and other worker movements around the world by harnessing the dynamism of the Internet and social media. Drawing on a combination of in‐depth semi‐structured interviews, documentary analysis, Google Analytics and social media data, the findings of this case study suggest that USI is successfully developing an international audience in the United States, the UK and Ireland. However, USI's ability to reach beyond English‐speaking countries and mobilise people to engage in collective action appears limited. The article makes an important contribution to the growing literature on social media in industrial relations through analysing the extent to which digital technologies can contribute to effective transnational labour solidarity.